Why I teach the controversy: using creationism to teach critical thinking - Honey, P. Lynne (Frontiers in Psychology, 2015)
Creationism and intelligent design are terms used to describe supernatural explanations for the origin of life, and the diversity of species on this planet. Many scientists have argued that the science classroom is no place for discussion of creationism. When I began teaching I did not teach creationism, as I focused instead on my areas of expertise. Over time it became clear that students had questions about creationism, and did not understand the difference between a scientific approach to knowledge and non-scientific approaches. This led me to wonder whether ignoring supernatural views allowed them to remain as viable ‘alternatives’ to scientific hypotheses, in the minds of students. Also, a psychology class is an ideal place to discuss not only the scientific method but also the cognitive errors associated with non-science views. I began to explain creationism in my classes, and to model the scientific thought process that leads to a rejection of creationism. My approach is consistent with research that demonstrates that teaching content alone is insufficient for students to develop critical thinking and my admittedly anecdotal experience leads me to conclude that ‘teaching the controversy’ has benefits for science students.